2014
DOI: 10.1080/10538712.2014.932878
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Narrative Practice Techniques on Child Behaviors in Forensic Interviews

Abstract: During investigations of child sexual abuse, forensic interviewers must maintain a delicate balance of providing support for the child while collecting forensic evidence about the abuse allegation required for credible evidence for court purposes. The use of narrative practice techniques can achieve both goals by creating conditions that facilitate the possibility that children will feel safe enough to provide detailed descriptions of the alleged abuse. This article reports findings from an evaluation of a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…The finding that children spoke more overall when their interview contained a practice narrative echoes the results of numerous studies with non-Aboriginal children (Anderson et al, 2014;Hershkowitz, 2009;Price et al, 2013;Roberts et al, 2004;Sternberg et al, 1997;Whiting, 2013). Conversely, the null finding regarding children's words per prompt is similar to previous laboratory findings with Aboriginal children (Hamilton et al, in press a), suggesting that practice narratives may not confer benefits to the accounts of all Aboriginal children, yet they also appear to do no harm.…”
Section: Practice Narrativessupporting
confidence: 73%
See 1 more Smart Citation
“…The finding that children spoke more overall when their interview contained a practice narrative echoes the results of numerous studies with non-Aboriginal children (Anderson et al, 2014;Hershkowitz, 2009;Price et al, 2013;Roberts et al, 2004;Sternberg et al, 1997;Whiting, 2013). Conversely, the null finding regarding children's words per prompt is similar to previous laboratory findings with Aboriginal children (Hamilton et al, in press a), suggesting that practice narratives may not confer benefits to the accounts of all Aboriginal children, yet they also appear to do no harm.…”
Section: Practice Narrativessupporting
confidence: 73%
“…It also provides the child with an opportunity to practice recounting memories and answering questions (predominantly open-ended: e.g., "Tell me more about that part"). Field and laboratory studies have both demonstrated that when a child is asked open-ended questions in the preparatory phase of the interview, the informativeness and/or accuracy of their subsequent accounts is improved (Anderson, Anderson, & Gilgun, 2014;Hershkowitz, 2009;Price, Roberts, & Collins, 2013;Roberts, Lamb, & Sternberg, 2004;Sternberg et al, 1997;Whiting, 2013). Research has also evinced that interviewers asked a greater proportion of open-ended prompts during the substantive phase of the interview when they had first conducted a practice narrative (Price et al, 2013).…”
Section: Practice Narrativementioning
confidence: 99%
“…In 2013, subsequent to research conducted at CornerHouse [76] and likely some challenges to their use of media and questioning strategies, CornerHouse substantially revised their interview structure [76,77]. Added components are "orienting messages", that is interview ground rules, the use of a narrative approach, and privileging an invitation to children of all ages to tell what they know about the interview and its purpose [78].…”
Section: The Revision Of the Cornerhouse Protocolmentioning
confidence: 99%
“…On the other hand, suggestive questioning produces shorter reports, which are more likely to be erroneous and may also produce false reports, particularly in preschool children (e.g. Anderson et al 2014;Craig et al 1999;Davies et al 2000;). …”
Section: Interviewer Techniques In Relation To the Quality And Quantimentioning
confidence: 99%
“…Contradictory or nonsensical responses, which can appear in response to suggestive questioning, may reduce the credibility of the children's account (e.g. Anderson et al 2014;Howie et al 2012;Lamb et al 2013). The detrimental effect of suggestive techniques on children's accuracy is often misused in an attempt to discredit children's testimonies and is likely to be used against the child in court (Goodman et al 1999).…”
Section: Suggestive Interviewingmentioning
confidence: 99%